Elemental and spectroscopic characterization of fractions of an acidic extract of oil sands process water - Jones, D.; Scarlett, Alan; West, C.; Frank, R.; Gieleciak, R.; Hager, D.; Pureveen, J.; Tegelaar, E.; Rowland, S. (2013)
'Naphthenic acids' (NAs) in petroleum produced water and oil sands process water (OSPW), have been implicated in toxicological effects. However, many are not well characterized. A method for fractionation of NAs of an OSPW was used herein and a multi-method characterization of the fractions conducted. The unfractionated OSPW acidic extract was characterized by elemental analysis, electrospray ionization-Orbitrap-mass spectrometry (ESI-MS), and an esterified extract by Fourier Transform infrared (FTIR) and ultraviolet-visible (UV) absorption spectroscopy and by comprehensive multidimensional gas chromatography-MS (GCxGC-MS). Methyl esters were fractionated by argentation solid phase extraction (Ag+ SPE) and fractions eluting with: hexane; diethyl ether: hexane and diethyl ether, examined. Each was weighed, examined by elemental analysis, FTIR, UV, GC-MS and GCxGC-MS (both nominal and high resolution MS). The ether fraction, containing sulfur, was also examined by GCxGC-sulfur chemiluminescence detection (GCxGC-SCD).The major ions detected by ESI-MS in the OSPW extract were assigned to alicyclic and aromatic 'O2' acids; sulfur was also present. Components recovered by Ag+ SPE were also methyl esters of alicyclic and aromatic acids; these contained little sulfur or nitrogen. FTIR spectra showed that hydroxy acids and sulfoxides were absent or minor. UV spectra, along with the C/H ratio, further confirmed the aromaticity of the hexane:ether eluate. The more minor ether eluate contained further aromatics and 1.5% sulfur. FTIR spectra indicated free carboxylic acids, in addition to esters. Four major sulfur compounds were detected by GCxGC-SCD. GCxGC-high resolution MS indicated these were methyl esters of C18 S-containing, diaromatics with =C3 carboxylic acid side chains. © 2013 Elsevier Ltd.